Structural and Electrochemical Properties of F-Doped RbTiOPO4 (RTP:F) Predicted from First Principles - Bocchini, Adriana; Xie, Yingjie; Schmidt, Wolf Gero; Gerstmann, Uwe (Crystals)
Batteries based on heavier alkali ions are considered promising candidates to substitute for current Li-based technologies. In this theoretical study, we characterize the structural properties of a novel material, i.e., F-doped RbTiOPO4 (RbTiPO4F, RTP:F), and discuss aspects of its electrochemical performance in Rb-ion batteries (RIBs) using density functional theory (DFT). According to our calculations, RTP:F is expected to retain the so-called KTiOPO4 (KTP)-type structure, with lattice parameters of 13.236 Å, 6.616 Å, and 10.945 Å. Due to the doping with F, the crystal features eight extra electrons per unit cell, whereby each of these electrons is trapped by one of the surrounding Ti atoms in the cell. Notably, the ground state of the system corresponds to a ferromagnetic spin configuration (i.e., S=4). The deintercalation of Rb leads to the oxidation of the Ti atoms in the cell (i.e., from Ti3+ to Ti4+) and to reduced magnetic moments. The material promises interesting electrochemical properties for the cathode: rather high average voltages above 2.8 V and modest volume shrinkages below 13% even in the fully deintercalated case are predicted.

14N Hyperfine and nuclear interactions of axial and basal NV centers in 4H-SiC: A high frequency (94 GHz) ENDOR study - Murzakhanov, F. F.; Sadovnikova, M. A.; Mamin, G. V.; Nagalyuk, S. S.; von Bardeleben, H. J.; Schmidt, Wolf Gero; Biktagirov, Timur; Gerstmann, Uwe; Soltamov, V. A. (Journal of Applied Physics)
The nitrogen-vacancy (NV) centers (NCVSi)− in 4H silicon carbide (SiC) constitute an ensemble of spin S = 1 solid state qubits interacting with the surrounding 14N and 29Si nuclei. As quantum applications based on a polarization transfer from the electron spin to the nuclei require the knowledge of the electron–nuclear interaction parameters, we have used high-frequency (94 GHz) electron–nuclear double resonance spectroscopy combined with first-principles density functional theory to investigate the hyperfine and nuclear quadrupole interactions of the basal and axial NV centers. We observed that the four inequivalent NV configurations (hk, kh, hh, and kk) exhibit different electron–nuclear interaction parameters, suggesting that each NV center may act as a separate optically addressable qubit. Finally, we rationalized the observed differences in terms of distinctions in the local atomic structures of the NV configurations. Thus, our results provide the basic knowledge for an extension of quantum protocols involving the 14N nuclear spin.

Synthesis of new graphene oxide/TiO2 and TiO2/SiO2 nanocomposites and their evaluation as photocatalysts - Rosenthal, Marta; Biktagirov, Timur; Schmidt, Wolf Gero; Wilhelm, René (Catalysis Science & Technology)
Composites of different graphene oxide types, TiO 2 materials, and especially synthetic routes influence the photocatalytic activity of the resulting material.

Adsorption of Cyclic (Alkyl) (Amino) Carbenes on Monohydride Si(001) Surfaces: Interface Bonding and Electronic Properties - Meier, Lukas; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, A.; Singh, Amit; Banh, Ngoc Chi; Richter, B.; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, B. (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: HRI; XAI; negation; understanding; explaining; touch interaction; gesture

Probabilistic Scoring Lists for Interpretable Machine Learning - Hanselle, Jonas Manuel; Fürnkranz, Johannes; Hüllermeier, Eyke (Discovery Science)

Tech/Imaginations (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

Cuando los muros hablan: Diálogos poéticos en las redes sociales - Descubrir dimensiones poéticas en el espacio digital para incorporarlas en el aula de lengua extranjera - del Valle, Victoria (Digitales Lehren und Lernen als Schnittstelle für die Kompetenzförderung im Spanischunterricht)

Europa im Fremdsprachenunterricht Französisch, Italienisch & Spanisch: Sprachenpolitik, Kulturpluralität und Mehrsprachigkeit

Technology Education considering children’s needs – Evidence-based development of Inclusive materials for learning with robots at primary level - Schröer, Franz; Tenberge, Claudia (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, Vol. 1 No. October (2023): PATT40 Proceedings)

Including: Thinking Towards an Inclusive Curriculum for Technology Education in German Primary Schools - Schröer, Franz; Tenberge, Claudia (Bloomsbury Handbook of Technology Education)
Keywords: Curriculum; Inclusion; Sachunterricht; Participation

Agentenbasierte Modellierung und Simulation im Pandemiemanagement - Hälterlein, Jens (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Mathematical models and computer simulations play a crucial role in the context of the COVID-19 crisis for knowledge about the possible course of the pandemic and for appropriate policy decisions. The paper presents results from an ethnographic study of a government-funded R & D project dealing with agent-based modeling and simulation (ABMS) in the context of pandemic management. Based on the assumption that the use of computer simulations in pandemic management is not only a means to an end for political or epidemiological goals but also plays a significant role in determining which goals and strategies appear politically legitimate, the paper reconstructs how insights into the pandemic are generated in ABMS and specifically in the researched project and made accessible for decision-making.
Keywords: General Medicine

"Dorische Welt" – Dorisches Europa? Ästhetischer Aristokratismus zwischen Poetologie und Weltanschauung in Gottfried Benns Essays 1933/34 - Heise, Tillmann (Liberalismus (be-)denken: Ideen von Europa in Wissenschaft, Literatur und Kulturkritik (1900–1950))

Liberalismus (be-)denken: Ideen von Europa in Wissenschaft, Literatur und Kulturkritik (1900–1950)

Dialogical Functions of You-Narration in Auto/Biography: Anne Harich’s “Wenn ich das gewußt hätte…”: Erinnerungen an Wolfgang Harich (2007) - Mildorf, Jarmila (Zagadnienia Rodzajów Literackich)

Forschungsdatenmanagement erleichtern durch relationale Datenbanken: Ein Datenmodell für naturwissenschaftsdidaktische Forschung - Buschütter, David; Zeller, Jannis; Oltmanns, Stefan; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Vogelsang, Christoph (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Writing as Narrative Resource in Therapeutic Settings: Diaries, Sketches, Notes - Mildorf, Jarmila; Ketteler, Daniel (Narrative and Mental Health Today: Reimagining Theory and Practice)

‘I had a patient who…’: Narratives of Vicarious Experience in GPs’ Discourse on Domestic Violence - Mildorf, Jarmila (Narrative Structure and Narrative Knowing in Medicine and Science)

Narratives and Mental Health: An Introduction - Mildorf, Jarmila; Punzi, Elisabeth; Singer, Christoph (Narrative and Mental Health: Reimagining Theory and Practice)

The Literary in Narrating Dramatic Life Experiences - Hatavara, Mari; Hyvärinen, Matti; Mildorf, Jarmila (The Routledge Companion to Literary Media)